Rothia dentocariosa Septicemia without Endocarditis in a Neonatal Infant with Meconium Aspiration Syndrome - Shin, Jeong Hwan (American Society for Microbiology, 2004)
Rothia dentocariosa, a gram-positive coccoid- to rod-shaped bacterium with irregular morphology, is a rare cause of bacteremia in patients without endocarditis. We report the first case of R. dentocariosa septicemia without endocarditis, which occurred in a neonatal infant with meconium aspiration syndrome.